2007
DOI: 10.2522/ptj.20060154
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Two Forms of Feedback on Training of a Joint Mobilization Skill by Using a Joint Translation Simulator

Abstract: Subjects who trained with augmented feedback had less variability, and thus more consistency, than the control group subjects who received no feedback. Augmented feedback provides the student with a reference force and the status of his or her performance. The effectiveness of the JTS feedback compared with no feedback was clearly demonstrated. Skill acquisition in mobilization can be enhanced by either concurrent or terminal feedback.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(44 citation statements)
references
References 31 publications
1
38
0
2
Order By: Relevance
“…Three studies used human participants who received the mobilization; 12,14,15 two used mechanical simulators. 13,16 These studies found that using concurrent or terminal feedback provided by the simulator helped PT learners to apply more accurate and consistent force during mobilizations [12][13][14][15][16] with less variability; 12 results were maintained 5 days 13 and 1 week after the intervention. 14 Only one study examined the long-term retention of the manual therapy skills, which was poor at 3-month follow-up.…”
Section: Data Synthesis and Analysismentioning
confidence: 97%
See 1 more Smart Citation
“…Three studies used human participants who received the mobilization; 12,14,15 two used mechanical simulators. 13,16 These studies found that using concurrent or terminal feedback provided by the simulator helped PT learners to apply more accurate and consistent force during mobilizations [12][13][14][15][16] with less variability; 12 results were maintained 5 days 13 and 1 week after the intervention. 14 Only one study examined the long-term retention of the manual therapy skills, which was poor at 3-month follow-up.…”
Section: Data Synthesis and Analysismentioning
confidence: 97%
“…Five studies examined simulation models to facilitate skill development in manual therapy mobilizations, four of which focused on performing a posterior-anterior (PA) lumbar spine mobilization [12][13][14][15][16] while the fifth simulated glenohumeral joint mobilization. In these studies, a simulator was used to quantify the mobilization forces by measuring the mean force exerted by the student through the plinth onto a force plate.…”
Section: Data Synthesis and Analysismentioning
confidence: 99%
“…In the study by Lee, Moseley, and Refshauge (1990), the concurrent feedback group also outperformed the no-feedback group (Lee et al, 1990). Chang, Chang, Chien, Chung, and Hsu (2007) reported that subjects benefited equally from terminal and concurrent feedback . Indeed, these studies in physical therapy showed that concurrent feedback can contribute to enhancement of motor learning.…”
Section: Visual Feedback In Complex Tasksmentioning
confidence: 99%
“…A control group receiving no feedback was not included in the study design, because it has been previously demonstrated that practice with concurrent feedback is better than no feedback. 9,32,50 Students attended a single practice session at which data were recorded for 10 seconds without feedback, and the average over the 10-second period was calculated for each force parameter. Data were recorded for each student pretest (before any feedback was given), followed by 12 practice trials of 30 seconds of grade II central PA mobilization to the L3 vertebra (while receiving feedback).…”
Section: Procedures and Data Collectionmentioning
confidence: 99%
“…15,17,32,39,50,54 However, comparisons between studies are difficult due to the variety of feedback methods and tasks examined. Chang et al 9 investigated types of feedback (concurrent versus terminal) for students learning joint mobilization and found that both types enhanced performance but neither was superior. Consistent with this, students in the self-controlled group of the current study chose a mixture of concurrent and terminal feedback, with 62.9% of all students reporting that they preferred to receive both types of feedback (TABLE 3).…”
Section: Feedback and Manual Therapymentioning
confidence: 99%